The relationship between dental anxiety and dental decay experience in antenatal mothers - Esa, R.; Savithri, V.; Humphris, G.; Freeman, R. (2010)
The aim of this study was to investigate the relationship between dental anxiety and dental decay experience among antenatal mothers attending Maternal and Child Health clinics in Malaysia. A cross-sectional study was conducted on a consecutive sample of 407 antenatal mothers in Seremban, Malaysia. The questionnaire consisted of participants' demographic profile and the Dental Fear Survey. The D(3cv)MFS was employed as the outcome measure and was assessed by a single examiner (intraclass correlation = 0.98). A structural equation model was designed to inspect the relationship between dental anxiety and dental decay experience. The mean Dental Fear Survey score for all participants was 35.1 95% confidence interval (34.0, 36.3). The mean D(3cv)MFS score was 10.8 95% confidence interval (9.5, 12.1). Participants from low socio-economic status groups had significantly higher D(3cv)MFS counts than those from high socio-economic status groups. The path model with dental anxiety and socio-economic status as predictors of D(3cv)MFS showed satisfactory fit. The correlation between dental anxiety and dental decay experience was 0.30 (standardized estimate), indicating a positive association. Socio-economic status was also statistically significantly associated with the D(3cv)MFS count (beta = 0.19). This study presented robust evidence for the significant relationship between dental anxiety and dental decay experience in antenatal mothers.